Confocal Laser Scanning Microscopy Based on a Silicon Photomultiplier for Multicolor In Vivo Imaging in Near‐Infrared Regions I and II. Issue 12 (9th November 2022) - Yan, Tianyu; Wang, Xinyu; Liu, Siting; Fan, Dawei; Xu, Xinyi; Zeng, Qi; Xie, Hui; Yang, Xiaoli; Zhu, Shouping; Ma, Xiaopeng; Yuan, Zhen; Chen, Xueli
Abstract: Confocal laser scanning microscopy (CLSM) is expected to exhibit a better imaging performance in the second near‐infrared (NIR‐II) windows with weak tissue scattering and autofluorescence. However, the indium gallium arsenide (InGaAs) detectors currently used for imaging in the NIR‐II region are prohibitively expensive, hampering its extensive biomedical applications. In this study, a novel NIR‐II CLSM system is developed by using the inexpensive silicon photomultiplier (SiPM) that can perform the multicolor biological imaging in vivo. Using IR‐780 iodide as the contrast agent, the NIR‐II imaging capability of constructed CLSM is inspected, demonstrating a spatial resolution of 1.68 µm (close to the diffraction limit) and a fluorophore detection sensitivity as low as 100 nm . In particular, it is discovered that the multicolor imaging performance in both NIR‐I and NIR‐II windows is comparable to those from multialkali and InGaAs photomultiplier tubes. In addition, 3D NIR‐II CLSM is also conducted for in vivo imaging of the vascular structure in mouse ear and subcutaneous tumors. To the best of authors' knowledge, this is the first time that a low‐cost detector based on a SiPM has been used for microscopic imaging of trailing fluorescence signals in the NIR‐II region of an NIR fluorescent probe. Abstract : Using IR‐780 as the contrast agent, the Silicon photomultiplier‐based detection scheme, a low‐cost and compact solution to confocal laser scanning microscopy, exhibited superior performance than photomultiplier tubes in the first near‐infrared and part of second near‐infrared regions, providing a spatial resolution approaching diffraction limit, the detection sensitivity of nanomolar fluorophores, and the capability of optical sectioning and 3D image reconstruction of living tissues.